2021
DOI: 10.1038/s41598-021-00464-7
|View full text |Cite
|
Sign up to set email alerts
|

Silica fertilization improved wheat performance and increased phosphorus concentrations during drought at the field scale

Abstract: Drought and the availability of mineable phosphorus minerals used for fertilization are two of the important issues agriculture is facing in the future. High phosphorus availability in soils is necessary to maintain high agricultural yields. Drought is one of the major threats for terrestrial ecosystem performance and crop production in future. Among the measures proposed to cope with the upcoming challenges of intensifying drought stress and to decrease the need for phosphorus fertilizer application is the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The research field of virtual soils is rapidly developing because of the need for improved climate‐adaption of agricultural crops or the crop yield enhancement through soil additives (e.g., Schaller et al., 2021). Soil–crop modeling could benefit from a coupling of a root architectural model with a soil model that allows for feedback loops between root growth, soil structure, soil water content, and nutrient concentration.…”
Section: Hillslope and Catchment Scale Soil Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The research field of virtual soils is rapidly developing because of the need for improved climate‐adaption of agricultural crops or the crop yield enhancement through soil additives (e.g., Schaller et al., 2021). Soil–crop modeling could benefit from a coupling of a root architectural model with a soil model that allows for feedback loops between root growth, soil structure, soil water content, and nutrient concentration.…”
Section: Hillslope and Catchment Scale Soil Modelingmentioning
confidence: 99%
“…The research field of virtual soils is rapidly developing because of the need for improved climate-adaption of agricultural crops or the crop yield enhancement through soil additives (e.g., Schaller et al, 2021).…”
Section: Application To Virtual Soilsmentioning
confidence: 99%
“…Besides direct effects of tissue Si on plant physiology, elevated soil Si might modulate soil processes, potentially explaining the positive growth responses of Si-fertilized plants under drought [19]. Experiments have shown that increasing biogenic amorphous Si in soils improves its water holding capacity [20], increasing water availability to plants [21]. Thus, to fully appreciate the role of elevated leaf Si as a drought-resistance mechanism it needs to be evaluated in isolation from potential soil Si effects.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of whether Si supplementation alleviates drought stress under field conditions is surprisingly rare. In wheat ( T. aestivum ), for example, there are only two studies to our knowledge ( Maghsoudi et al., 2016 ; Schaller et al., 2021 ). These studies showed that Si supplementation generally had beneficial effects on wheat growing under drought conditions, including increased water use efficiency ( Maghsoudi et al., 2016 ) and photosynthetic activity ( Schaller et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In wheat ( T. aestivum ), for example, there are only two studies to our knowledge ( Maghsoudi et al., 2016 ; Schaller et al., 2021 ). These studies showed that Si supplementation generally had beneficial effects on wheat growing under drought conditions, including increased water use efficiency ( Maghsoudi et al., 2016 ) and photosynthetic activity ( Schaller et al., 2021 ). Both field studies supplemented naturally dry field sites with irrigation but did not manipulate exposure to rainfall.…”
Section: Introductionmentioning
confidence: 99%